PERAN GURU AGAMA ISLAM DALAM MENANAMKAN MODERASI BERAGAMA MELALUI PROGRAM PEMBIASAAN DI SMPN 1 PARONGPONG KABUPATEN BANDUNG BARAT - Fitria Hidayat; Maslani; Supiana (Jurnal Al-Karim : Jurnal Pendidikan, Psikologi dan Studi Islam, 2021)
In order to create a conducive learning atmosphere, it is necessary to foster the ethics of tolerance between students in order to realize harmony between religious people and not to discriminate against different religions. Therefore, it is necessary to play an important role of a teacher in fostering the ethics of tolerance of students among religious people. Because teachers not only act as teachers but also as educators, mediators, evaluators, motivators, facilitators in fostering, shaping and preparing mental students or students actively carry out their duties and are expected to provide stability in the face of various possibilities even in the direction of the worst possibilities, namely shocks and psychic tensions. The purpose of this research is to find out and analyze how the role of Islamic teachers in instilling religious moderation towards students at SMPN 1 Parongpong West Bandung Regency. So that life is harmonious in learning despite different religions and beliefs. The results of this study show that Islamic Education Teachers (GPAI) at SMPN 1 Parongpong Barat in instilling religious tolerance by habituating daily religion, this is implemented in several activities in schools.